Secondary battery, pole piece thereof and aqueous binder

By developing a water-based binder containing a variety of natural and synthetic materials, the problem of environmental pollution of traditional organic solvent-based binders is solved, and a high-performance and environmentally friendly production process of battery pole sheets is achieved.

CN119581558AInactive Publication Date: 2025-03-07CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311462255.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-06
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional organic solvent-based binders have problems with volatile organic compounds emissions and environmental pollution during the production process, which affects sustainable development and ecological and environmental protection.

Method used

A water-based binder was developed, including styrene butadiene rubber (SBR), polyethylene oxide (PEO), sodium carboxymethylcellulose (CMC), sodium alginate (SA), chitosan (CTS), guar gum (GG), lignin, sericin and gluten, as the binder for secondary battery pole sheets.

Benefits of technology

This water-based adhesive can significantly improve the mechanical performance and cycle life of the battery pole, reduce environmental pollution, and is cheap and has a wide range of sources, making it suitable for commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581558A_ABST
    Figure CN119581558A_ABST
Patent Text Reader

Abstract

The invention discloses a binder for a secondary battery pole piece. The binder comprises at least one of styrene butadiene rubber (SBR), polyethylene oxide (PEO), sodium carboxymethyl cellulose (CMC), sodium alginate (SA), chitosan (CTS), guar gum (GG), lignin and sericin, and vital gluten. The wheat gluten is mainly applied to the food industry and the feed industry, and a brand new application field of the wheat gluten is developed. And the vital gluten is rich in various organic functional groups and is used as a main component of the binder, so that the binder can greatly improve the electrical properties of the positive and negative electrode materials. The invention also discloses a pole piece containing the binder and a secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to an adhesive for secondary battery pole pieces. Background Art Secondary batteries are a type of battery that can be charged and discharged repeatedly. They can be used repeatedly and are an important energy storage solution for many modern electronic devices and vehicles. In the positive and negative electrodes of secondary batteries, binders are key components. Binders play a bonding role between the positive and negative active materials and the electrode current collectors, allowing the active materials to be firmly attached to the surface of the electrode current collector, thereby ensuring the stability and cycle performance of the electrodes.

[0002] Traditional binders usually use organic solvent-based binders, such as polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyvinylidene fluoride (PVDF), etc. These organic solvent-based binders have problems of volatile organic compound emissions and environmental pollution during the production process, which is not conducive to sustainable development and ecological protection. Therefore, the development of water-based binders has become an important research direction in the field of secondary batteries.

[0003] Aqueous binders mainly refer to binders that use water as a solvent. Compared with organic solvent-based binders, they have the following advantages: (1) Water is an environmentally friendly solvent that has little impact on the environment during use and disposal. It can effectively reduce the emission of volatile organic compounds and help reduce air pollution; (2) Aqueous binders are less likely to cause safety problems such as fire and explosion during production and use, and are safer and more reliable than organic solvent-based binders; (3) Water is a widely available resource. Compared with expensive organic solvents, using water as a solvent can reduce production costs; (4) The research and development of aqueous binders is also expected to improve the conductivity and ion transport performance of batteries, further improving the energy density and cycle life of batteries. Therefore, the development of aqueous binders has become a research hotspot in the field of secondary batteries. Summary of the invention

[0004] The first object of the present invention is to provide a water-based adhesive for secondary battery pole pieces.

[0005] The second object of the present invention is to provide a secondary battery electrode and a method for preparing the same.

[0006] A third object of the present invention is to provide a secondary battery.

[0007] To achieve the above objectives, the present invention provides the following specific technical solutions.

[0008] First, the present invention provides a water-based binder for a secondary battery electrode, comprising at least one of styrene-butadiene rubber (SBR), polyethylene oxide (PEO), sodium carboxymethyl cellulose (CMC), sodium alginate (SA), chitosan (CTS), guar gum (GG), lignin, and sericin, and gluten.

[0009] In a further preferred embodiment, the amount of gluten in the aqueous binder is a, 5wt%≤a<100wt%.

[0010] In a further preferred embodiment, the aqueous binder comprises 5 wt % of SBR and 95 wt % of gluten.

[0011] In a further preferred embodiment, the aqueous binder comprises 20 wt % of PEO and 80 wt % of gluten.

[0012] In a further preferred embodiment, the aqueous binder comprises 15 wt % of CMC and 85 wt % of gluten.

[0013] In a further preferred embodiment, the aqueous binder comprises 40 wt % of SA and 60 wt % of gluten.

[0014] In a further preferred embodiment, the aqueous binder comprises 20 wt % of CTS and 80 wt % of gluten.

[0015] In a further preferred embodiment, the aqueous binder comprises 50 wt % of GG and 50 wt % of gluten.

[0016] In a further preferred embodiment, the aqueous binder comprises 25 wt % of lignin and 75 wt % of gluten.

[0017] In a further preferred embodiment, the aqueous binder comprises 30 wt % of sericin and 70 wt % of gluten.

[0018] Secondly, the present invention provides a pole piece of a secondary battery, wherein the pole piece includes the aforementioned water-based binder.

[0019] The present invention further provides a method for preparing the electrode sheet of the secondary battery, comprising the following steps: The battery active material, the conductive agent and the aforementioned aqueous binder are mixed evenly to obtain a dry mix; Adding deionized water to the dry mixture and stirring to obtain electrode slurry; The electrode slurry is evenly coated on the current collector to obtain a wet electrode sheet; The wet electrode sheet is dried to obtain the electrode sheet of the secondary battery.

[0020] In a further preferred embodiment, the battery active material is one of a lithium battery positive electrode material, a lithium battery negative electrode material, a sodium battery positive electrode material, a sodium battery negative electrode material, a potassium battery positive electrode material, and a potassium battery negative electrode material.

[0021] In a further preferred embodiment, the conductive agent includes at least one of carbon black, conductive graphite, acetylene black, Super P, graphene, carbon nanotubes, Ketjen black, and carbon fiber.

[0022] In a further preferred embodiment, the mass ratio of the battery active material, the conductive agent, and the aqueous binder is 6.5-9.5: 0.25-1.5: 0.3-1.55.

[0023] In a further preferred embodiment, the current collector is one of a positive electrode current collector and a negative electrode current collector; the positive electrode current collector is one of aluminum foil, stainless steel mesh, and titanium foil; the negative electrode current collector is one of copper foil and titanium foil.

[0024] Based on the same inventive concept, the present invention provides a secondary battery including the above-mentioned electrode sheet.

[0025] The present invention has the following obvious beneficial effects: Wheat gluten is mainly composed of gliadin with a small molecular weight, spherical shape and good extensibility and glutenin with a large molecular weight, fibrous shape and strong elasticity, and is mainly used in the food industry and feed industry. The present invention opens up a new application field for wheat gluten. Wheat gluten is rich in various organic functional groups. As the main component of the binder, the binder can greatly improve the electrochemical performance of the positive and negative electrode materials.

[0026] Using a binder with gluten as the main component, the recycling and disassembly process of retired batteries is more convenient and easy.

[0027] As the main component of the aqueous binder for the electrodes of secondary batteries, gluten powder has low cost, wide sources, strong universality, and is environmentally friendly, and has strong commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 These are SEM images of the pole piece prepared in Example 1 at different magnifications.

[0029] Figure 2 These are SEM images of the pole piece prepared in comparative example 1-1 at different magnifications.

[0030] Figure 3 It is a comparison chart of the electrochemical performance of the batteries assembled from Example 1 and Comparative Examples 1-1 to 1-3.

[0031] Figure 4It is a comparison chart of the electrochemical performance of the batteries assembled from Example 2 and Comparative Examples 2-1 to 2-3.

[0032] Figure 5 It is a comparison chart of the electrochemical performance of the batteries assembled from Example 3, Comparative Example 3-1 and Comparative Example 3-2.

[0033] Figure 6 It is a comparison chart of the electrochemical performance of the batteries assembled from Example 4, Comparative Example 4-1 and Comparative Example 4-2.

[0034] Figure 7 It is a comparison chart of the electrochemical performance of the batteries assembled from Example 5, Comparative Example 5-1 and Comparative Example 5-2.

[0035] Figure 8 It is a comparison chart of the electrochemical performance of the batteries assembled from Example 6, Comparative Example 6-1 and Comparative Example 6-2.

[0036] Fig. 9 It is a comparison chart of the electrochemical performance of the batteries assembled from Example 7, Comparative Example 7-1 and Comparative Example 7-2.

[0037] Fig.10 It is a comparison chart of the electrochemical performance of the batteries assembled from Example 8, Comparative Example 8-1 and Comparative Example 8-2. DETAILED DESCRIPTION

[0038] The present invention provides a water-based binder for a secondary battery pole piece, comprising at least one of styrene-butadiene rubber (SBR), polyethylene oxide (PEO), sodium carboxymethyl cellulose (CMC), sodium alginate (SA), chitosan (CTS), guar gum (GG), lignin, sericin and gluten powder.

[0039] Styrene-butadiene rubber (SBR), polyethylene oxide (PEO), sodium carboxymethyl cellulose (CMC), sodium alginate (SA), chitosan (CTS), guar gum (GG), lignin, and sericin are also commonly used aqueous binders. Further adding gluten to these aqueous binders can, on the one hand, significantly enhance the mechanical properties of battery electrodes; on the other hand, gluten has a strong wire drawing and networking function, which can produce a significant coating effect on the battery active materials and greatly improve the cycle life of the battery; in addition, gluten contains a large amount of protein and has many organic groups, which can effectively inhibit the oxidative decomposition of the electrolyte and improve the stability of the battery system.

[0040] In the specific practice, gluten can be used as the main component of the water-based adhesive. In some preferred embodiments of the present invention, the amount of gluten in the water-based adhesive is a, 5wt%≤a<100wt%.

[0041] In some preferred embodiments of the present invention, a water-based binder having the following composition is further selected: 5wt% SBR and 95wt% gluten; 20wt% PEO and 80wt% gluten; 15wt% CMC and 85wt% gluten; 40wt% SA and 60wt% gluten; 20wt% CTS and 80wt% gluten; 50wt% GG and 50wt% gluten; 25wt% lignin and 75wt% gluten; 30wt% sericin and 70wt% gluten.

[0042] Secondly, the present invention provides a pole piece of a secondary battery, wherein the pole piece includes the aforementioned water-based binder.

[0043] A method for preparing the electrode sheet of the secondary battery is further provided, comprising the following steps: The battery active material, the conductive agent and the aforementioned aqueous binder are mixed evenly to obtain a dry mix; Adding deionized water to the dry mixture and stirring to obtain electrode slurry; The electrode slurry is evenly coated on the current collector to obtain a wet electrode sheet; The wet electrode sheet is dried to obtain the electrode sheet of the secondary battery.

[0044] The aqueous binder provided by the present invention is suitable for almost all positive and negative electrode materials, including but not limited to lithium battery positive electrode materials, lithium battery negative electrode materials, sodium battery positive electrode materials, sodium battery negative electrode materials, potassium battery positive electrode materials, and potassium battery negative electrode materials. Lithium battery positive electrode materials include but are not limited to LiFeMnPO 4 、LiFe x Mn y PO 4 (x+y=1), Li 2 MnO 4 、LiCoO 2 、LiNi x Co y Mn z O 2 (x+y+z=1), LiNi x Co y Al z O 2(x+y+z=1), lithium-rich manganese-based positive electrode materials, and positive electrode materials for lithium-sulfur batteries. Lithium battery negative electrode materials include but are not limited to graphite, silicon carbon, pure silicon, etc. Sodium battery positive electrode materials include but are not limited to sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium nickel manganate, etc. Sodium battery negative electrode materials include but are not limited to hard carbon.

[0045] The conductive agent used in the pole piece is a conventional conductive agent in the art, including but not limited to carbon black, conductive graphite, acetylene black, Super P, graphene, carbon nanotubes, Ketjen black, and carbon fiber. The current collector used in the pole piece is also a conventional current collector in the art, such as a positive current collector and a negative current collector; the positive current collector includes aluminum foil, stainless steel mesh, and titanium foil; the negative current collector includes copper foil and titanium foil.

[0046] In some preferred embodiments of the present invention, the mass ratio of the battery active material, the conductive agent, and the aqueous binder is 6.5-9.5: 0.25-1.5: 0.3-1.55.

[0047] Based on the same inventive concept, the present invention provides a secondary battery including the above-mentioned electrode sheet.

[0048] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0049] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0050] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0051] Example 1 (1) Preparation of water-based binder Weigh 5% of SBR and 95% of gluten powder, mix them evenly, and then obtain a water-based binder.

[0052] (2) Preparation of electrode 0.40 g of the battery active material LiCoO 2 , 0.05 g of conductive agent acetylene black, and 0.05 g of the aqueous binder described in step (1) are mixed evenly to obtain a dry mixture; Adding a certain amount of deionized water to the dry mixture, stirring to prepare the slurry, and obtaining electrode slurry; The electrode slurry is evenly coated on the aluminum current collector to obtain a wet electrode sheet; The wet electrode sheet is dried at 70°C to obtain an electrode sheet.

[0053] (3) Assembling batteries The positive electrode sheet in (2) was matched with the lithium metal negative electrode and the commercial electrolyte (1M LiPF 6 The button cells were assembled in an inert glove box in a DEC:FEC solvent with a volume ratio of 1:1. The assembled cells were subjected to cycle tests.

[0054] Comparative Example 1-1 The only difference between Comparative Example 1-1 and Example 1 is that the binder is an oil-based binder polyvinylidene fluoride PVDF.

[0055] Comparative Example 1-2 The difference between Comparative Example 1-2 and Example 1 is that the binder is 100% SBR.

[0056] Comparative Examples 1-3 The difference between Comparative Examples 1-3 and Example 1 is that the binder is 100% gluten powder.

[0057] Figure 1 This is the SEM image of the pole piece prepared in Example 1. Figure 2 This is the SEM image of the pole piece obtained in Comparative Example 1-1. Figure 1 and Figure 2 It can be seen that the electrode sheet made with 5% SBR and 95% gluten as binder is flat and dense. 2 The positive electrode material is obviously coated in the network of the binder. However, the surface of the electrode sheet made with PVDF as the binder is rough, and most of the positive electrode particles float on the surface, in a bare and unbonded state. This shows that gluten powder can fully exert its bonding effect as a water-based binder.

[0058] Figure 3 The cycle performance curves of the batteries assembled from Example 1 and Comparative Examples 1-1, 1-2 and 1-3 show that the battery with 5% SBR and 95% gluten as the binder shows the best cycle performance. The specific analysis is as follows: The battery assembled in Example 1 maintained a capacity of 186.1 mAh g after 100 cycles at a high voltage of 3-4.6 V. -1 The average specific capacity is 198.9 mAh g -1 The battery assembled in comparative example 1-1 had only 105.1 mAhg after 100 cycles. -1 The average specific capacity is 159.7 mAh g -1; The performance of the batteries assembled in Comparative Examples 1-2 and Comparative Examples 1-3 decays very quickly, and the capacity decays significantly after 100 cycles, especially when SBR is used as a binder, the capacity is almost reduced to 0. It can be seen that the use of a water-based binder composed of 5% SBR and 95% gluten as a binder for the electrode can significantly improve the electrical performance of the battery compared with an oil-based binder. In addition, it also shows that there is a synergistic effect between SBR and gluten, which can further improve the electrical performance of the electrode.

[0059] Example 2 (1) Preparation of water-based binder Weigh 20% of PEO and 80% of gluten powder, mix them evenly, and then obtain a water-based adhesive.

[0060] (2) Preparation of electrode 0.40 g of the battery active material LiFePO 4 , 0.05 g of conductive agent acetylene black, and 0.05 g of the aqueous binder described in step (1) are mixed evenly to obtain a dry mixture; Adding a certain amount of deionized water to the dry mixture, stirring to prepare the slurry, and obtaining electrode slurry; The electrode slurry is evenly coated on the aluminum current collector to obtain a wet electrode sheet; The wet electrode sheet is dried at 70°C to obtain an electrode sheet.

[0061] (3) Assembling batteries The positive electrode sheet in (2) was matched with the lithium metal negative electrode and the commercial electrolyte (1M LiPF 6 The button cells were assembled in an inert glove box in a DEC: FEC solvent with a volume ratio of 1:1. The assembled cells were subjected to cycle tests.

[0062] Comparative Example 2-1 The only difference between Comparative Example 2-1 and Example 2 is that the binder is an oil-based binder polyvinylidene fluoride PVDF.

[0063] Comparative Example 2-2 The only difference between Comparative Example 2-2 and Example 2 is that the binder is 100% PEO.

[0064] Comparative Examples 2-3 The difference between Comparative Example 2-3 and Example 2 is that the binder is 100% gluten powder.

[0065] Figure 4The cycle performance curves of the batteries assembled from Example 2 and Comparative Examples 2-1, 2-2, and 2-3 show that 20% PEO and 80% gluten binder show the best cycle stability compared with PVDF, 100% PEO, and 100% gluten binder, and the specific capacity after 100 cycles is 153.5 mAh g -1 , with an average capacity of 155.5 mAh g -1 , almost no capacity decay, and the retention rate is as high as 98.8%. The performance of the three comparative examples is as follows: Comparative Example 2-1 has a specific capacity of 144.1 mAh g after 100 cycles -1 , with an average capacity of 147.9 mAh g -1 ; Comparative Example 2-2 has a specific capacity of 113.1 mAh g after 100 cycles -1 , with an average capacity of 130.9 mAh g -1 ; The specific capacity of comparative example 2-3 after 100 cycles is 139.1 mAh g -1 , with an average capacity of 143.6 mAh g -1 .

[0066] Example 3 (1) Preparation of water-based binder Weigh 15% of CMC and 85% of gluten powder, mix them evenly, and then you get a water-based binder.

[0067] (2) Preparation of electrode 0.48 g of a graphite negative electrode as a battery active material, 0.06 g of a conductive agent Super P, and 0.06 g of the aqueous binder described in step (1) are mixed evenly to obtain a dry mixture; Adding a certain amount of deionized water to the dry mixture, stirring to prepare the slurry, and obtaining electrode slurry; The electrode slurry is evenly coated on the copper current collector to obtain a wet electrode sheet; The wet electrode sheet is dried at 80°C to obtain an electrode sheet.

[0068] (3) Assembling batteries The graphite anode electrode sheet in (2) was matched with the lithium metal anode and the commercial electrolyte (1M LiPF 6 The coin cells were assembled in an inert glove box in a DEC:FEC solvent (1:1 by volume).

[0069] Comparative Example 3-1 The only difference between Comparative Example 3-1 and Example 3 is that the binder is 100% CMC.

[0070] Comparative Example 3-2 The difference between Comparative Example 3-2 and Example 3 is that the binder is 100% gluten powder.

[0071] Figure 5 The cycle performance curves of the batteries assembled in Example 3 and Comparative Examples 3-1 and 3-2 show that the graphite anode matched with 15% CMC and 85% gluten binder exhibits the best electrochemical performance, and the specific capacity is still as high as 263.9 mAh g after 300 cycles. -1 The capacity retention rate was 94.64%. In contrast, the cycling performance of 100% CMC and 100% gluten powder was much worse, with the specific capacities after 300 cycles being 110.6 and 182.1 mAh g, respectively. -1 , the capacity retention rates are 42.42% and 68.51% respectively.

[0072] Example 4 (1) Preparation of water-based binder Weigh 40% of SA and 60% of gluten powder, mix them evenly, and then obtain a water-based binder.

[0073] (2) Preparation of electrode 0.56 g of active material silicon-carbon negative electrode (silicon accounts for 20%), 0.07 g of conductive agent Super P, and 0.07 g of the aqueous binder described in step (1) are mixed evenly to obtain a dry mixture; Adding a certain amount of deionized water to the dry mixture, stirring to prepare the slurry, and obtaining electrode slurry; The electrode slurry is evenly coated on the copper current collector to obtain a wet electrode sheet; The wet electrode sheet is dried at 80°C to obtain an electrode sheet.

[0074] (3) Assembling batteries The silicon-carbon anode electrode sheet in (2) was matched with the lithium metal anode and the commercial electrolyte (1M LiPF 6 The coin cells were assembled in an inert glove box in a DEC:FEC solvent (1:1 by volume).

[0075] Comparative Example 4-1 The only difference between Comparative Example 4 and Example 4 is that the binder contains 100% SA.

[0076] Comparative Example 4-2 The only difference between Comparative Example 4-2 and Example 4 is that the binder contains 100% gluten powder.

[0077] Figure 6The cycle performance curves of the batteries assembled from Example 4 and Comparative Examples 4-1 and 4-2 show that the silicon-carbon anode matched with 40% SA and 60% gluten binder exhibits the best electrochemical performance, and the specific capacity is still as high as 373 mAh g after 300 cycles. -1 , with an average capacity of up to 361.6 mAh g -1 In contrast, the cycling performance of 100% SA and 100% gluten powder is much worse, with specific capacities of 164.8 and 268.2 mAhg after 300 cycles, respectively. -1 , with average capacities of 251.3 and 291.1 mAh g -1 .

[0078] Example 5 (1) Preparation of water-based binder Weigh 25% of lignin and 75% of gluten powder, mix them evenly, and then obtain a water-based binder.

[0079] (2) Preparation of electrode 0.48 g of hard carbon, a sodium negative electrode active material, 0.06 g of acetylene black, a conductive agent, and 0.06 g of the aqueous binder described in step (1) are mixed evenly to obtain a dry mixture; Adding a certain amount of deionized water to the dry mixture, stirring to prepare the slurry, and obtaining electrode slurry; The electrode slurry is evenly coated on the copper current collector to obtain a wet electrode sheet; The wet electrode sheet is dried at 80°C to obtain an electrode sheet.

[0080] (3) Assembling batteries The hard carbon anode electrode sheet in (2) was matched with a sodium metal anode and a commercial electrolyte (1M NaPF 6 The coin cells were assembled in an inert glove box in a DEC:FEC solvent (1:1 by volume).

[0081] Comparative Example 5-1 The only difference between Comparative Example 5-1 and Example 5 is that the binder is 100% lignin.

[0082] Comparative Example 5-2 The difference between Comparative Example 5-2 and Example 5 is that the binder is 100% gluten powder.

[0083] Figure 7 The cycle performance curves of the batteries assembled from Example 5 and Comparative Examples 5-1 and 5-2 show that the hard carbon anode matched with 25% lignin and 75% gluten binder exhibits the best electrochemical performance, and the specific capacity is still as high as 286.3 mAh g after 100 cycles.-1 The capacity retention rate was 98.97%. In contrast, the cycling performance of 100% lignin and 100% gluten powder was much worse, with the specific capacities after 100 cycles being 203.9 and 245.3 mAh g, respectively. -1 , the capacity retention rates are 74.63% and 89.19% respectively.

[0084] Example 6 (1) Preparation of water-based binder Weigh 20% of CTS and 80% of gluten powder, mix them evenly, and then obtain a water-based adhesive.

[0085] (2) Preparation of electrode 0.48 g of sodium vanadium phosphate, a sodium positive electrode active material, 0.06 g of acetylene black, a conductive agent, and 0.06 g of the aqueous binder described in step (1) are mixed evenly to obtain a dry mixture; Adding a certain amount of deionized water to the dry mixture, stirring to prepare the slurry, and obtaining electrode slurry; The electrode slurry is evenly coated on the aluminum current collector to obtain a wet electrode sheet; The wet electrode sheet is dried at 80°C to obtain an electrode sheet.

[0086] (3) Assembling batteries The sodium positive electrode sodium vanadium phosphate electrode sheet in (2) is matched with the sodium metal negative electrode and the commercial electrolyte (1M NaPF 6 The coin cells were assembled in an inert glove box in a DEC:FEC solvent (1:1 by volume).

[0087] Comparative Example 6-1 The only difference between Comparative Example 6-1 and Example 6 is that the binder is 100% CTS.

[0088] Comparative Example 6-2 The only difference between Comparative Example 6-2 and Example 6 is that the binder is 100% of rice flour.

[0089] Figure 8 The cycle performance curves of the batteries assembled from Example 6 and Comparative Examples 6-1 and 6-2 show that the sodium vanadium phosphate positive electrode matched with 20% CTS and 80% gluten binder exhibits the best electrochemical performance, and the specific capacity is still as high as 89.4 mAh g after 100 cycles. -1 The capacity retention rate was 93.77%. In contrast, the cycling performance of 100% CTS and 100% gluten powder was much worse, with the specific capacities after 100 cycles being 58.6 and 79.3 mAh g, respectively. -1 , the capacity retention rates are 66.36% and 87.93% respectively.

[0090] Example 7 (1) Preparation of water-based binder Weigh 50% of GG and 50% of gluten powder, mix them evenly, and then you can get a water-based binder.

[0091] (2) Preparation of electrode 0.48 g of sodium vanadium fluorophosphate, a sodium positive electrode active material, 0.06 g of acetylene black, a conductive agent, and 0.06 g of the aqueous binder described in step (1) are mixed evenly to obtain a dry blend; Adding a certain amount of deionized water to the dry mixture, stirring to prepare the slurry, and obtaining electrode slurry; The electrode slurry is evenly coated on the aluminum current collector to obtain a wet electrode sheet; The wet electrode sheet is dried at 80°C to obtain an electrode sheet.

[0092] (3) Assembling batteries The vanadium fluorophosphate positive electrode sheet in (2) was matched with the sodium metal negative electrode and the commercial electrolyte (1M NaPF 6 The coin cells were assembled in an inert glove box in a DEC / FEC solvent (1:1 by volume).

[0093] Comparative Example 7-1 The only difference between Comparative Example 7-1 and Example 7 is that the binder is 100% GG.

[0094] Comparative Example 7-2 The only difference between Comparative Example 7-2 and Example 7 is that the binder is 100% gluten powder.

[0095] Fig. 9 The cycle performance curves of the batteries assembled from Example 7 and Comparative Examples 7-1 and 7-2 show that the sodium vanadium fluorophosphate positive electrode matched with 50% GG and 50% gluten binder exhibits the best electrochemical performance, and the specific capacity is still as high as 95.3 mAh g after 100 cycles. -1 The capacity retention rate was 97.97%. In contrast, the cycling performance of 100% GG and 100% gluten powder was much worse, with the specific capacities after 100 cycles being 35.9 and 70.4 mAh g, respectively. -1 , the capacity retention rates are 41.08% and 78.05% respectively.

[0096] Example 8 (1) Preparation of water-based binder Weigh 30% of sericin and 70% of gluten powder, mix them evenly, and obtain a water-based adhesive.

[0097] (2) Preparation of electrode 0.48 g of 1 μm pure silicon, 0.06 g of conductive agent acetylene black, and 0.06 g of the aqueous binder described in step (1) are mixed evenly to obtain a dry mixture; Adding a certain amount of deionized water to the dry mixture, stirring to prepare the slurry, and obtaining electrode slurry; The electrode slurry is evenly coated on the copper current collector to obtain a wet electrode sheet; The wet electrode sheet is dried at 80°C to obtain an electrode sheet.

[0098] (3) Assembling batteries The pure silicon anode electrode sheet in (2) was matched with the lithium metal anode and commercial electrolyte (1M LiPF 6 The coin cells were assembled in an inert glove box in a DEC / FEC solvent (1:1 by volume).

[0099] Comparative Example 8-1 The only difference between Comparative Example 8-1 and Example 8 is that the binder is 100% sericin.

[0100] Comparative Example 8-2 The only difference between Comparative Example 8-2 and Example 8 is that the binder is 100% gluten powder.

[0101] Fig.10 The cycle performance curves of the batteries assembled from Example 8 and Comparative Examples 8-1 and 8-2 show that the 1-micron pure silicon anode matched with 30% sericin and 70% gluten binder exhibits the best electrochemical performance, and the specific capacity is still as high as 2270 mAh g after 100 cycles. -1 The capacity retention rate was 88.43%. In contrast, the cycling performance of 100% GG and 100% gluten powder was much worse, with the specific capacities after 100 cycles being 750 and 1747 mAh g, respectively. -1 , the capacity retention rates are 33.56% and 74.63% respectively.

[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A water-based adhesive for a secondary battery electrode, characterized in that: The invention comprises at least one of styrene-butadiene rubber (SBR), polyethylene oxide (PEO), sodium carboxymethyl cellulose (CMC), sodium alginate (SA), chitosan (CTS), guar gum (GG), lignin, sericin and gluten powder.

2. The aqueous adhesive for a secondary battery electrode according to claim 1, characterized in that: The amount of gluten in the water-based bonding agent is a, 5wt%≤a<100wt%.

3. The aqueous binder for a secondary battery electrode according to claim 1 or 2, characterized in that: The water-based binder includes 5 wt % of SBR and 95 wt % of gluten.

4. The aqueous binder for a secondary battery electrode according to claim 1 or 2, characterized in that: The water-based binder includes 20 wt % of PEO and 80 wt % of gluten.

5. The aqueous binder for a secondary battery electrode according to claim 1 or 2, characterized in that: The water-based binder includes 15 wt % of CMC and 85 wt % of gluten.

6. The aqueous binder for a secondary battery electrode according to claim 1 or 2, characterized in that: The aqueous binder includes 40 wt % of SA and 60 wt % of gluten.

7. The aqueous binder for a secondary battery electrode according to claim 1 or 2, characterized in that: The water-based binder includes 20 wt % of CTS and 80 wt % of gluten.

8. The aqueous binder for a secondary battery electrode according to claim 1 or 2, characterized in that: The aqueous binder includes 50 wt % of GG and 50 wt % of gluten.

9. The aqueous binder for a secondary battery electrode according to claim 1 or 2, characterized in that: The aqueous binder comprises 25 wt % of lignin and 75 wt % of gluten.

10. The aqueous binder for a secondary battery electrode according to claim 1 or 2, characterized in that: The water-based adhesive includes 30 wt % of sericin and 70 wt % of gluten.

11. A pole piece of a secondary battery, characterized in that: The electrode sheet includes the aqueous binder for the secondary battery electrode sheet according to any one of claims 1 to 10.

12. A method for preparing a pole piece of a secondary battery, characterized in that: The following steps are involved: The battery active material, the conductive agent, and the aqueous binder for the secondary battery pole piece according to any one of claims 1 to 10 are uniformly mixed to obtain a dry mixture; Adding deionized water to the dry mixture and stirring to obtain electrode slurry; The electrode slurry is evenly coated on the current collector to obtain a wet electrode sheet; The wet electrode sheet is dried to obtain the electrode sheet of the secondary battery.

13. A secondary battery, characterized in that: Including the pole piece according to claim 11 or the pole piece prepared by the preparation method according to claim 12.

Citation Information

Patent Citations

  • Direct mixing type aqueous binder system, positive plate and sodium ion battery

    CN116463089A

  • Binder, electrode and electrochemical capacitor

    JP2016066755A

  • Binder composition for nonaqueous secondary battery electrode, slurry composition for nonaqueous secondary battery electrode, nonaqueous secondary battery electrode, and nonaqueous secondary battery

    JP2017069063A

  • Method of producing electrode

    JP2017111970A

  • Starch-based battery system

    US20110293968A1